Method for producing cement mixture
Patent Information
- Application Number
- JP2025002363
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-11-24
- Filing Date
- 2025-01-07
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-03-26
AI Technical Summary
【0056】 本発明によれば、コンクリート等のセメント硬化物の塩素含有率の上昇を抑制しつつ、バイオマス灰を有効に活用することが可能となる。
Smart Images

Figure 2025036740000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a cement mixture containing biomass ash powder and a method for producing the same. [Background technology]
[0002] In recent years, with the backdrop of a shortage of disposal sites, it is hoped that the incineration ash generated by the incineration of municipal waste will be recycled as a cement raw material, etc. In addition, various efforts toward the spread of renewable energy have led to the construction and operation of biomass power generation facilities, and the amount of incineration ash (biomass ash) generated from biomass power generation is also increasing. For this reason, it is hoped that biomass ash will also be recycled as a cement raw material, etc., in the same way as incineration ash from municipal waste, etc.
[0003] In relation to such issues, for example, Non-Patent Document 1 below discusses the application of biomass ash to cement admixtures. [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] Takahiro Sagawa et al., "Application of wood biomass incineration ash to cement admixtures", Abstracts of the 70th Cement Technology Conference, 2016
[1307] Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, from the viewpoint of environmental conservation, materials to replace mountain sand and river sand are desired as aggregates used in the manufacture of concrete. On the other hand, biomass such as palm stalks has been attracting attention as a carbon-neutral fuel, and its usage is on the rise. This trend has led to the generation of a large amount of biomass ash. Therefore, in order to prevent the shortage of biomass ash disposal sites, there is a demand for the utilization of biomass ash. Therefore, the present inventors are considering the use of biomass ash as an alternative material for aggregates.
[0006] In the above-mentioned non-patent document 1, the incineration ash obtained by burning wood biomass alone was classified using a sieve with a classification point of 90 μm, and the compressive strength of a mortar specimen obtained by substituting the sieve residue (coarse powder) for 10% of the fine aggregate material was verified.
[0007] However, biomass ash contains a large amount of chlorine. If the fine aggregate substitute obtained by the method described in Non-Patent Document 1 is used to produce concrete, the chlorine content of the concrete may exceed the regulated value, and in some cases, this may cause corrosion of reinforcing bars.
[0008] An object of the present invention is to provide a technique that can effectively utilize biomass ash while suppressing an increase in the chlorine content of cement mixtures such as concrete. [Means for solving the problem]
[0009] The biomass ash powder or granular material according to the present invention is characterized in that the cumulative volume percentage of particle size distribution at 10% (D10) is 35 μm or more.
[0010] According to the above-mentioned configuration, biomass ash powdered material with a suppressed chlorine (Cl) content is realized. When this biomass ash powdered material is used as a partial substitute for fine aggregate to produce a cement mixture, it is possible to suppress an increase in the amount of chlorine contained in the resulting cement mixture. In other words, the biomass ash powdered material may be used to replace fine aggregate for a cement mixture.
[0011] In this specification, the term "cement mixture" refers to a concept including concrete and mortar, and includes both a pre-hardened state and a hardened state. In addition, the term "hardened cement product" refers to the state of the cement mixture after it has been hardened.
[0012] Among biomass ash, coarse powder with a relatively large particle size has a lower content of calcium, sulfur, chlorine, and carbon than fine powder with a relatively small particle size. Therefore, by setting D10 to 35 μm or more, a biomass powder with a low chlorine content (chlorine concentration) can be obtained. More preferably, the D10 of the biomass ash powder is 50 μm to 115 μm. By setting D10 of the biomass ash powder to 115 μm or less, the action as a binder (pozzolanic reaction) can be expected, so that the strength of the hardened cement can be ensured. From the same viewpoint, it is preferable that the value (D90) at which the cumulative volume percentage of the particle size distribution of the biomass ash powder is 90% is set to 80 μm to 400 μm.
[0013] The particle size distribution of the biomass ash powder or granular material has a cumulative volume percentage of 50% (D50) of preferably 100 μm to 300 μm, more preferably 150 μm to 250 μm, and particularly preferably 175 μm to 200 μm.
[0014] The particle size distribution of the biomass ash powder or granule can be measured, for example, by a laser diffraction / scattering type particle size distribution measuring device.
[0015] The chlorine (Cl) content of the biomass ash powder is preferably 0.1 mass % or less, and more preferably 0.05 mass % or less.
[0016] The proportion of chlorine contained in the biomass ash powder or granule can be measured by a known method, and preferred examples of such methods include wet quantitative analysis and a calibration curve method using an X-ray fluorescence analyzer.
[0017] The biomass ash powder or granule is preferably a powder or granule having an amorphous content of 60 mass % or less.
[0018] As described above, the biomass ash powder has a D10 of 35 μm or more, and has a larger particle size than the cement used in the production of a cement mixture. If the proportion of amorphous matter contained in the biomass ash powder having such a particle size increases, when a cement mixture is produced using this biomass ash powder, the reactivity with alkali metals (Na, K) increases, the amount of alkali silica gel generated increases, and the durability decreases due to the water absorption and expansion associated with this reaction (alkali-silica reaction). By setting the proportion of amorphous matter contained in the biomass ash powder to 60 mass% or less, the reactivity with alkali metals decreases, making it difficult for the alkali-silica reaction to occur. The alkali-silica reaction is also called the "alkali aggregate reaction."
[0019] From the above viewpoint, the proportion of amorphous matter contained in the biomass ash powder or granule is more preferably 50% by mass or less, further preferably 40% by mass or less, and particularly preferably 30% by mass or less.
[0020] The proportion of amorphous matter contained in the biomass ash powder or granule can be measured, for example, by a method of calculating the results of X-ray diffraction measurement by Rietveld analysis (XRD-Rietveld method).
[0021] The content of SO3 contained in the biomass ash powder is preferably 1% by mass or less, more preferably 0.5% by mass or less, and particularly preferably 0.2% by mass or less. If the content of SO3 contained in the biomass ash powder exceeds 1% by mass, when the biomass ash powder is used for producing a cement mixture, it may have an effect on the quality of the hardened cement product, such as abnormal expansion.
[0022] The content of SO3 contained in the biomass ash powder or granule can be measured by a known method, and preferable examples thereof include wet quantitative analysis and a calibration curve using an X-ray fluorescence analyzer.
[0023] The ignition loss of the biomass ash powder granules is preferably 3% by mass or less, and particularly preferably 2% by mass or less. If the ignition loss of the biomass ash powder granules exceeds 3% by mass, the amount of unburned carbon increases, and when used in the production of a cement kneaded body, the biomass ash powder granules may adsorb chemical admixtures added to the kneaded body, adversely affecting the fluidity and air content, or cause blackening of the obtained hardened cement.
[0024] The ignition loss of the biomass ash granules can be measured by a known method, and a preferred example of the method is a method conforming to JIS R 5202 "Method of Chemical Analysis of Cement."
[0025] The cement kneaded body according to the present invention comprises cement and fine aggregate, The fine aggregate is characterized in that 5% by mass to 40% by mass of the biomass powder and granules is contained.
[0026] According to the above-mentioned configuration, a cement mixture in which a part of the fine aggregate is replaced with the biomass ash powder and granules, while an increase in the chlorine content is suppressed, is realized.
[0027] However, the particle size of the biomass ash powder is finer than that of general fine aggregates specified in JIS A 5005 "Crushed stone and crushed sand for concrete". Therefore, if the biomass ash powder is mixed at a ratio of more than 40% by mass of the total fine aggregate, the ratio of fine powder contained in the fine aggregate will be too high, which may affect the fluidity of the cement mixture. On the other hand, if the biomass ash powder is mixed at a ratio of less than 5% by mass of the total fine aggregate, biomass ash, which is being generated in increasing amounts, cannot be fully utilized.
[0028] The method for producing a cement kneaded body according to the present invention comprises the steps of: (a) classifying biomass ash into coarse powder and fine powder; The method further comprises a step (b) of mixing the coarse powder obtained in the step (a) with cement and water without grinding the coarse powder.
[0029] The coarse powder classified in step (a) is a relatively large particle size of the biomass ash, and therefore has a lower chlorine content than the fine powder. As a result, even if the coarse powder is used as a substitute for fine aggregate to produce a cement mix, the chlorine content in the resulting cement mix can be kept within the regulated value.
[0030] This step (a) is preferably performed on biomass ash (preferably dry ash) in a state where water has not been added and the hydrate formation reaction has not progressed. For example, if the biomass ash is wet ash and has aggregated or formed hydrates, there is a possibility that the coarse powder side will contain a large amount of chlorine even after classification.
[0031] In this specification, "dry ash" refers to biomass ash that is collected in a dry state, to which water has not been added before classification, and to which no aggregation or hydrates have been formed. The dry ash also includes the case where water has been added before classification, but in which a large amount of water has been added and the ash has been dispersed, and no hydrates have been formed due to long-term storage. In this specification, "wet ash" refers to, for example, bottom ash, which is the incineration residue discharged from the bottom of an incinerator, or fly ash collected by a dust collector, which has been collected in a state containing moisture by being cooled with water or sprayed with water, or which has been dried. Generally, wet ash has a moisture content of 15% by mass or more.
[0032] When carrying out the step (a), any device can be used as long as it can classify the biomass ash at a classification point on the order of μm, and for example, a sieve, a gravity settling device, an inertial classifier, a centrifugal classifier, a gravity classifier, etc. can be suitably used, and from the viewpoint of classification accuracy, it is particularly preferable to use a cyclone type air separator, a vortex type centrifugal classifier, a sieving device, etc. In this case, it is preferable to classify the biomass ash using a reference value in the range of 30 μm to 100 μm as a classification point.
[0033] The step (b) may be a step of mixing the coarse powder with an adjusting powder so that the proportion of amorphous matter in the mixture of the coarse powder and the adjusting powder is adjusted to 60 mass% or less, and then mixing the mixture with cement and water.
[0034] For example, if the amorphous content of the coarse powder obtained after classification exceeds 60% by mass, the amorphous content of the entire mixture can be reduced to 60% by mass or less by mixing in an adjustment powder with a low amorphous content (such as other biomass ash). By using this mixture as a partial replacement for fine aggregate, expansion due to alkali-silica reaction is less likely to occur.
[0035] The method for producing the cement kneaded body further includes a step (c) of washing the coarse powder obtained in the step (a), The step (b) may be a step of mixing the coarse powder after being washed with water in the step (c).
[0036] This makes it possible to further reduce the chlorine, alkali metal, and sulfur components contained in the coarse powder, and also to reduce the amounts of heavy metals such as selenium and chromium that may pollute the environment, and calcium oxide and calcium hydroxide that are easily reactive.
[0037] The water-washing step (c) preferably includes a step (c1) of adding water to the biomass ash to form a slurry, a step (c2) of supplying wash water to the slurry to wash it, and a step (c3) of dewatering the slurry after washing. Since the dehydrated material is obtained by washing the biomass ash after forming the slurry and then dewatering it, chlorine and heavy metals can be removed.
[0038] The method for producing a cement kneaded product may further include a step (d) of oxidizing the biomass ash during or after the step (c).
[0039] According to this method, the pH during washing is adjusted to the acidic side, so that chlorine can be removed more efficiently. In addition, even if the biomass ash contains a large amount of easily reactive calcium oxide or calcium hydroxide, it can be completely replaced with calcium carbonate or calcium sulfate, so that the quality of the cement mixture before hardening, such as its fluidity, can be homogenized.
[0040] In this step (d), an acid solution may be added during the washing of the biomass ash, or a gas containing carbon dioxide (CO2) may be blown into the biomass ash after the washing process. In particular, by using combustion exhaust gas from a cement kiln, chlorine bypass extraction gas, or combustion exhaust gas from a biomass incineration facility or a biomass power plant as the CO2-containing gas, the CO2 contained in these gases can be converted into calcium carbonate and fixed in the biomass ash, which is expected to have an effect of reducing CO2 emissions. In addition, the sulfur oxides (SO x Harmful gases such as sulphur dioxide and toluene can also be converted into calcium sulfate and fixed in the biomass ash.
[0041] In particular, in step (d), by subjecting the biomass ash to carbonation treatment during the water washing in step (c), calcium contained in large amounts in the wastewater after water washing can be precipitated as calcium carbonate, thereby suppressing the generation of scale, thereby suppressing blockage of pipes for wastewater treatment.
[0042] The method for producing a cement kneaded product may further include a step (e) of removing unburned carbon contained in the biomass ash during the execution of the step (c).
[0043] Biomass ash (raw ash) may contain a large amount of unburned carbon. Therefore, when biomass ash containing a large amount of carbon is used as a substitute for fine aggregate, the hardened cement product may become blackened, or the chemical admixture may be adsorbed by the carbon, reducing the fluidity of the cement mixture before hardening and reducing the air content.
[0044] In contrast, according to the above-mentioned method, the unburned carbon can be removed during washing with water, so that the above-mentioned problems can be prevented. Specifically, the amount of unburned carbon contained in the ore can be reduced by mixing an unburned carbon removing agent such as oil or a surfactant and performing flotation.
[0045] Further, the cement kneaded body and the cement manufacturing method according to the present invention include the above-mentioned cement kneaded body manufacturing method, The method is characterized by comprising a step (f1) of feeding the fine powder obtained in the step (a) to at least one of a cement clinker raw material to be fed into a cement kiln, cement clinker obtained from the cement kiln, or cement obtained after a grinding treatment of the cement clinker.
[0046] Biomass ash has low activity, but the finer the particle size, the more active it is and the higher the alkali metal content. Therefore, as in the above method, the fine powder obtained after classifying biomass ash is mixed with cement clinker raw material, cement clinker (hereinafter, both may be collectively referred to as "cement raw material"), or cement, and the reaction is activated. Therefore, the strength of the hardened cement product is higher than when biomass ash before classification is added to cement raw material or cement.
[0047] In other words, according to the above method, the coarse powder with a relatively low chlorine content is used as a partial substitute for fine aggregate, and the fine powder with a relatively high chlorine content is used as a partial substitute for cement raw material or cement mixture, thereby making it possible to effectively utilize the biomass ash without leaving any of it behind.
[0048] When fine powder from classified biomass ash is added during cement production, cement with a high alkali metal content may be produced. When this cement is mixed with aggregate to produce a hardened cement product (concrete), there is a risk of alkali-silica reaction occurring. In response to this, the alkali-silica reaction can be suppressed by adding latent hydraulic substances such as blast furnace slag or pozzolans (including natural pozzolans such as silica powder and stone powder, and artificial pozzolans such as fly ash and calcined clay) together with the fine powder.
[0049] When the amorphous ratio of the biomass ash powder or granules (coarse powder) exceeds 60% by mass, or when the replacement rate of fine aggregate of the biomass ash powder or granules exceeds 40% by mass, at least one of a latent hydraulic substance and a pozzolan may be mixed as an admixture in the step (b) from the viewpoint of suppressing the alkali-silica reaction.
[0050] The method for producing the cement kneaded body and cement includes a step (c) of washing the biomass ash with water before or after the step (a), The step (f1) may be a step of adding the fine powder after it has been washed with water in the step (c).
[0051] According to the study by the present inventors, when comparing the coarse powder and fine powder obtained after classifying biomass ash, it was confirmed that most of the chlorine contained in the biomass ash is contained in the fine powder. Therefore, since chlorine, which is a cement-repellent component, is efficiently removed from the biomass ash after washing with water, it can be used as a cement raw material or in cement to suppress corrosion of reinforcing bars in concrete.
[0052] The method for producing the hardened cement product and the cement includes a step (g) of pulverizing the coarse powder obtained in the step (a) having an amorphous content of more than 60 mass%, The method may further include a step (f2) of introducing the coarse powder pulverized in the step (g) into at least one of the cement clinker raw material, the cement clinker, or the cement obtained after the cement clinker is pulverized.
[0053] When the proportion of amorphous matter contained in the coarse powder obtained after classification of biomass ash is high, exceeding 60% by mass, there is a risk of an alkali-silica reaction occurring when this coarse powder is used as a partial substitute for fine aggregate. On the other hand, the coarse powder obtained after classification of biomass ash has low calcium, sulfur, chlorine, and carbon contents and is close to the composition of coal ash, so that when used as a cement clinker raw material, homogeneity compared to conventional clinker raw materials can be ensured. In particular, since the content of sulfur and chlorine is low, coating is unlikely to be generated in the cement kiln, and there is an effect that the load on the chlorine bypass is unlikely to increase. Even when used as an admixture, the content of sulfur, chlorine, and carbon, which affect the quality of concrete, is low, and it can be used as a cement admixture or concrete admixture whose reactivity has been increased by grinding.
[0054] Specific methods for the steps (f1) and (f2) include feeding into raw material blending equipment such as a mixer or a grinder for blending raw materials for cement clinker, feeding into a preheater top or a calciner in front of a cement kiln (rotary kiln), feeding into the bottom of a cement kiln, feeding into the front of a cement kiln, feeding into a clinker cooler for cooling the cement clinker obtained by burning, feeding into a grinding device (mill) for grinding cement clinker, feeding into a mixer for producing blended cement, feeding into a concrete mixer, and the like.
[0055] When the proportion of amorphous matter in the coarse powder exceeds 60 mass %, the coarse powder may be added to the cement clinker raw material without being pulverized. Effect of the Invention
[0056] According to the present invention, it is possible to effectively utilize biomass ash while suppressing an increase in the chlorine content of hardened cement products such as concrete. [Brief description of the drawings]
[0057] [Figure 1] 1 is a diagram showing a process flow of a first embodiment of a method for producing a cement mix and cement. [Diagram 2] 2 is a block diagram showing a schematic configuration of a manufacturing system that implements the process flow shown in FIG. 1. [Diagram 3] 1 is a graph showing the particle size distribution of incineration fly ash obtained from the biomass power generation facility P1 used in Verification 1. [Figure 4] 1 is a diagram showing a process flow of a second embodiment of a method for producing a cement mix and cement. [Diagram 5] 1 is a diagram illustrating an example of a detailed processing flow of a water washing step. [Figure 6] FIG. 5 is a block diagram illustrating a schematic configuration of a manufacturing system that implements the process flow shown in FIG. [Figure 7] FIG. 7 is a block diagram showing a schematic example of the structure of the washing facility in FIG. 6. [Figure 8] FIG. 5 is a diagram illustrating an example of a process flow when a water washing step, an oxidation step, and an unburned carbon removal step are performed in the manufacturing method shown in FIG. 4. [Figure 9] FIG. 7 is a block diagram showing a schematic diagram of another example of the structure of the washing facility in FIG. 6. [Figure 10] 1 is a diagram showing a schematic diagram of another process flow of the second embodiment of the method for producing a cement mix and cement. [Figure 11] FIG. 11 is a block diagram illustrating a schematic configuration of a manufacturing system that implements the process flow shown in FIG. [Figure 12] FIG. 11 is a diagram illustrating an example of a process flow in the case where an oxidation step and an unburned carbon removal step are performed together with a water washing step in the manufacturing method shown in FIG. 10. [Figure 13] 11 is a block diagram showing a schematic configuration of another manufacturing system for carrying out the process flow shown in FIG. 10. [Figure 14] 1 is a diagram showing a process flow of a third embodiment of a method for producing a cement mix and cement. [Figure 15]FIG. 15 is a block diagram illustrating a schematic configuration of a manufacturing system that implements the process flow shown in FIG. 14. [Figure 16] 1 is a polarizing microscope image of biomass ash. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0058] [First embodiment] A first embodiment of the cement kneaded body and the method for producing cement according to the present invention will be described. The biomass ash powder and granules envisioned by the present invention will also be described in this section.
[0059] Fig. 1 is a diagram showing a typical process flow of a first embodiment of a method for producing a cement mix and cement, and Fig. 2 is a block diagram showing a typical structure of a system for carrying out this production method.
[0060] The manufacturing system 1 shown in FIG. 2 includes a raw material tank 3 in which cement clinker raw material Y1 is stored, a powder storage tank 5 in which biomass ash B1 is stored, a clinker manufacturing facility 10, a classification facility 20, a crushing facility 31, and a mixing facility 33.
[0061] The biomass ash B1 to which the present invention is applicable includes biomass incineration ash in general, such as ash from plants and bamboo, and ash from food waste. Biomass ash contains water-soluble alkali metal chlorides, alkali metal sulfates, and alkali metal carbonates. Biomass ash has the advantage of having a higher proportion of alkali metal sulfates and alkali metal carbonates and a lower concentration of alkali chlorides than municipal waste incineration ash and chlorine bypass dust.
[0062] In this embodiment, after the biomass ash B1 is classified, it is assumed that it is added to the production process of cement Cn2 (including the production process of cement clinker Cn1) as described below, or to the production process of cement kneaded body Cn3.
[0063] The K2O content of the biomass ash B1 is preferably 2% by mass to 10% by mass, more preferably 3% by mass to 8% by mass, and even more preferably 3% by mass to 5% by mass. If the K2O content of the biomass ash is less than 2% by mass, the strength of the cement may be reduced when used as an admixture, and there is a possibility that the necessary amount of the material to be added to the cement may not be secured in the first place. On the other hand, if the K2O content of the biomass ash exceeds 10% by mass, the amount of use when used as a raw material for cement clinker may be limited, or the occurrence of alkali-silica reaction may increase when used as an admixture.
[0064] The total alkali concentration in the biomass ash B1 is preferably 2% by mass to 11% by mass, more preferably 3% by mass to 6% by mass, calculated as R2O (R2O=Na2O+0.658×K2O). The sulfur oxide (SO3) concentration in the biomass ash is preferably 0.5% by mass to 6% by mass, more preferably 1% by mass to 5% by mass.
[0065] In biomass power plants, biomass and coal may be mixed and burned together, and the biomass ash B1 to which the present invention is applied also includes ash produced when such mixed combustion is performed. However, since coal ash produced by burning coal generally has a low K2O content, the activity of the biomass ash differs depending on the amount of coal used during mixed combustion. Therefore, when mixed with coal, it is preferable that the ash be obtained from a fuel with a biomass ratio of 50% by mass or more.
[0066] As biomass ash B1, palm kernel shell ash (PKS ash) obtained by using palm kernel shells as fuel among the incineration ash of plants and bamboo is a suitable example. Palm kernel shells are a by-product of palm oil production and are mainly used in the natural biomass energy industry. Palm kernel shells are a yellowish-brown fibrous material with low ash content, with particle sizes of about 5mm to 40mm and a calorific value of about 4000Kcal / kg. Therefore, in energy production using renewable resources, palm kernel shells have been increasingly used as fuel for biomass power generation in recent years.
[0067] Generally, there are stoker-type and fluidized bed-type combustion furnaces for biomass power generation, and in the case of circulating fluidized bed-type and pressurized fluidized bed-type combustion furnaces, limestone is added to perform desulfurization in the furnace. Biomass ash from such combustion furnaces contains a large amount of calcium and sulfur components, and the CaO content is generally 5% by mass to 45% by mass, for example. In addition, the form of Ca compounds derived from the added limestone includes CaO (quicklime), Ca(OH)2 (slaked lime), CaCO3 (calcium carbonate), CaSO4 (gypsum), etc. In addition, sand is added as a fluidizing medium, and the form of minerals derived from the added sand includes quartz and feldspar.
[0068] Biomass ash B1 may be bottom ash remaining at the bottom of a combustion furnace for biomass power generation, or fly ash obtained by collecting soot suspended in the combustion exhaust gas in a dry state using a dust collector. Of these, fly ash is preferable because it has higher concentrations of alkali metals and chlorine, and chlorine can be easily and efficiently separated by classification and washing with water.
[0069] Moreover, the biomass ash B1 is preferably dry ash. Once water is sprayed on the biomass ash, it may become granular, or chlorine may be incorporated into the hydrates produced, making it difficult to separate the chlorine by classification or washing with water. For example, it is preferable that the dry ash does not detect Friedel's salt or ettringite, which are hydrates, by powder X-ray diffraction. Alternatively, the moisture content is preferably 10% by mass or less, more preferably 5% by mass or less. Alternatively, the ignition loss is preferably 10% or less. The moisture content can be determined as the mass loss rate when dried at 105°C. The ignition loss can be determined as the mass loss rate when an object dried at 105°C is heated at 975°C.
[0070] From the viewpoint of increasing the strength of the cement mixture, the biomass ash B1 preferably has a median particle size (D50) of 200 μm or less, more preferably 150 μm or less, and even more preferably 90 μm or less. The particle size can be measured using a laser diffraction / scattering type particle size distribution measuring device, for example, MW3300EXII manufactured by Microtrack Bell Co., Ltd., using ethanol as a dispersion medium, and measuring after ultrasonic dispersion for 1 minute. Note that D50 means the value at which the cumulative volume percentage of the particle size distribution is 50%.
[0071] The clinker production facility 10 is a facility that produces cement clinker Cn1 by burning a cement clinker raw material Y1, and includes a cement kiln 12 for burning, a preheater 11 that heats the cement clinker raw material Y1 in advance before it is charged into the cement kiln 12, and a clinker cooler 13 that cools the burned cement clinker Cn1.
[0072] The pulverizing equipment 31 is equipment for mixing and pulverizing the cement clinker Cn1, optionally together with gypsum or the like, to produce fine-grained cement Cn2, and may be a general mill such as a tube mill that is used in the finishing process.
[0073] The mixing equipment 33 is a facility that mixes cement Cn2, water W1, fine aggregate FA, and coarse aggregate CA to generate a cement mixture Cn3, and is configured with a known mixer. The mixing equipment 33 is installed, for example, in a concrete factory. Here, the cement mixture Cn3 is concrete.
[0074] 1, the manufacturing method of this embodiment includes a step S10 of classifying biomass ash B1, a step S20 of adding the classified coarse powder B1C to the manufacturing process of cement kneaded body Cn3, and a step S30 of adding the classified fine powder B1F to the manufacturing process of cement Cn2. In the following, the adding or adding steps are collectively referred to as the "adding" step.
[0075] (Classification process S10) The biomass ash B1 stored in the powder storage tank 5 is classified by the classification equipment 20 into coarse powder B1C having a coarse particle size and fine powder B1F having a fine particle size based on a predetermined classification point.
[0076] The classification point determined in the classification step S10 is preferably in the range of 30 μm to 100 μm, more preferably in the range of 30 μm to 90 μm, and particularly preferably in the range of 38 μm to 75 μm.
[0077] The classification equipment 20 is not particularly limited as long as it is an equipment capable of classifying the biomass ash B1 at the classification points of the order of μm as described above, and for example, a sieve, a gravitational settling device, an inertial classifier, a centrifugal classifier, a gravity type classifier, etc. can be suitably used, and in particular, from the viewpoint of classification accuracy, it is preferable to use a cyclone type air separator, a vortex type centrifugal classifier, a sieving device, etc. Note that, as described later in the second embodiment, when the water washing step S40 is performed, it is efficient to perform the classification by a wet method.
[0078] In a fluidized bed incinerator, sand mainly composed of quartz as a fluidizing medium and limestone for desulfurization are charged. Fly ash of biomass ash from such an incinerator contains relatively coarse molten solidified or aggregated glass and sand-derived materials, relatively fine volatilized alkali metal salts, the above-mentioned limestone-derived materials, and fine glass particles. Therefore, if the particle size distribution of biomass ash is expressed as a frequency, and the classification point is set between the peaks on the fine particle side and the peaks on the coarse particle side, chlorine, sulfur, and calcium can be efficiently separated.
[0079] FIG. 3 is a graph showing the particle size distribution of the incineration fly ash obtained from the biomass power generation facility P1, which is used in the verification 1 described later. According to the graph in FIG. 3, it is confirmed that a peak with a high frequency value appears on the fine powder side, which has a relatively fine particle size, and on the coarse powder side, which has a relatively coarse particle size. It is considered that the fine powder side is derived from lime and alkali metal salts, and the coarse powder side is derived from quartz and feldspar. Therefore, it can be seen that chlorine, sulfur, and calcium can be efficiently separated by classifying the particle size of the area (valley area) between these peaks as a classification point. In some cases, a fluidized bed incinerator is equipped with equipment for recovering incineration ash that has settled in the boiler, air preheater, and high-temperature gas flow path, and equipment for recovering incineration ash such as a cyclone and a bag filter. Since the particle sizes of the incineration ash recovered by these recovery equipment are different, it is possible to replace the classifier by separating and recovering them.
[0080] A storage tank for the biomass ash B1 may be attached to the classification equipment 20. Furthermore, a supply device for quantitatively supplying the biomass ash B1 from the storage tank to the classification equipment 20 may be attached. These storage tanks and supply devices may be used appropriately depending on the state of the received biomass ash B1.
[0081] The first criterion for classification in the classification step S10 is the particle size of the coarse powder B1C obtained after classification. Specifically, the coarse powder B1C obtained after classification is classified in the classification step S10 so that the particle size has a D10 value of 35 μm or more. More preferably, the coarse powder B1C after classification has a D10 value of 50 μm to 115 μm.
[0082] The median particle size (D50) of the coarse powder B1C is preferably 100 μm to 300 μm, more preferably 150 μm to 250 μm, and particularly preferably 175 μm to 200 μm. The particle size D90 of the coarse powder B1C is preferably 80 μm to 400 μm.
[0083] According to the coarse powder B1C having the above particle size distribution, the chlorine (Cl) content is typically reduced to 0.2 mass% or less. The chlorine content of the coarse powder B1C is preferably 0.01 mass% to 0.1 mass%, and more preferably 0.01 mass% to 0.05 mass%.
[0084] The chlorine concentration ratio (chlorine content ratio) of the fine powder B1F to the coarse powder B1C is preferably 4 or more, more preferably 8 or more, and even more preferably 12 or more. The chlorine content of the fine powder B1F is typically 0.2 mass% to 2 mass%, and more typically 0.3 mass% to 1.5 mass%. That is, by this classification step S10, the biomass ash B1 (raw ash) is separated into the coarse powder B1C having a relatively low chlorine content and the fine powder B1F having a relatively high chlorine content.
[0085] Other criteria for classification in the classification step S10 include the amorphous content, activity index, yield, sulfur oxide (SO3) concentration, calcium oxide (CaO) concentration, and ignition loss.
[0086] The coarse powder B1C obtained after classification typically has an amorphous content of 60% by mass or less. The amorphous content of the coarse powder B1C is preferably 50% by mass or less, more preferably 40% by mass or less, and particularly preferably 30% by mass or less. The amorphous content of the fine powder B1F is typically 50% by mass to 80% by mass, and more typically 60% by mass to 70% by mass. That is, the classification step S10 separates the coarse powder B1C having a relatively low amorphous content from the fine powder B1F having a relatively high amorphous content. This point will be described later with reference to the examples.
[0087] The activity index of the fine powder B1F obtained in the classification step S10 is higher than that of the biomass ash (raw ash) B1, typically 70% or more in 7 days and 65% or more in 28 days, and more typically 75% or more in 7 days and 70% or more in 28 days. The activity index contained in the biomass ash B1 (B1C, B1F) can be measured by a known method, and a preferred example is a method based on JISA 6201:2015 "Fly ash for concrete".
[0088] The yield of the fine powder B1F is preferably 10% by mass to 80% by mass, more preferably 20% by mass to 70% by mass, and even more preferably 30% by mass to 60% by mass. The yield of the fine powder B1F may be the ratio of the total mass of the obtained fine powder B1F to the total mass of the biomass ash B1 before the classification step S10 is performed. On the other hand, the yield of the coarse powder B1C is preferably 20% by mass to 90% by mass, more preferably 30% by mass to 80% by mass, and even more preferably 40% by mass to 70% by mass.
[0089] The total alkali concentration ratio of the fine powder B1F to the coarse powder B1C is preferably 1.05 or more, more preferably 1.1 or more, and even more preferably 1.2 or more, calculated as R2O (R2O=Na2O+0.658×K2O). The total alkali concentration of the fine powder B1F is, for example, typically 2% by mass to 10% by mass, more typically 3% by mass to 8% by mass. On the other hand, the total alkali concentration of the coarse powder B1C is typically reduced to 0.5% by mass to 6% by mass, more typically 2% by mass to 5% by mass. The total alkali concentration contained in the biomass ash B1 (B1C, B1F) can be measured by a known method, such as wet quantitative analysis or a calibration curve using a fluorescent X-ray device. Similar methods can be used to measure the concentrations of chlorine, sulfur oxides, calcium oxide, and the like.
[0090] The ratio of the sulfur oxide (SO3) content of the fine powder B1F to that of the coarse powder B1C is preferably 5 or more, more preferably 10 or more, and even more preferably 20 or more. The sulfur oxide content of the fine powder B1F is, for example, typically 1 mass% to 6 mass%, more typically 2 mass% to 5 mass%. On the other hand, the sulfur oxide content of the coarse powder B1C is typically reduced to 1 mass% or less, more preferably 0.5 mass% or less, and particularly preferably 0.2 mass% or less.
[0091] The calcium oxide concentration ratio of the fine powder B1F to the coarse powder B1C is preferably 1.5 or more, more preferably 2 or more, and even more preferably 3 or more. The calcium oxide concentration of the fine powder B1F is, for example, typically 8% by mass to 40% by mass, and more typically 15% by mass to 35% by mass. On the other hand, the calcium oxide concentration of the coarse powder B1C is typically reduced to 3% by mass to 15% by mass, and more typically reduced to 5% by mass to 10% by mass.
[0092] The ignition loss of the coarse powder B1C is preferably 3% by mass or less, and particularly preferably 2% by mass or less. On the other hand, the ignition loss of the fine powder B1F is typically 5% by mass to 15% by mass, and more typically 5% by mass to 10% by mass. That is, the classification step S10 separates the coarse powder B1C, which has a relatively low ignition loss, from the fine powder B1F, which has a relatively high ignition loss. The ignition loss of the biomass ash B1 (B1C, B1F) can be measured by a known method, and a preferred example is a method conforming to JIS R 5202 "Chemical Analysis Method for Cement".
[0093] This classification step S10 corresponds to step (a), and the coarse powder B1C obtained in this classification step S10 corresponds to the "biomass ash powder and granular material."
[0094] (Injection process S20: During cement mix production) The coarse powder B1C obtained in the classification step S10 is added as a partial substitute for the fine aggregate FA when producing a cement mixture Cn3 such as concrete. The example in Fig. 2 shows a case in which the coarse powder B1C is mixed together with the cement Cn2, water W1, the fine aggregate FA, and the coarse aggregate CA in the mixing equipment 33. As described above, a general mixer is used as the mixing equipment 33.
[0095] When producing the cement kneaded body Cn3, the substitution rate of the coarse powder B1C to the fine aggregate FA is preferably 5 mass% to 40 mass%, more preferably 10 mass% to 30 mass%, and particularly preferably 15 mass% to 25 mass%.
[0096] As described above, the coarse powder B1C separated from the biomass ash (raw ash) B1 in the classification step S10 has a low chlorine content. Therefore, even if the coarse powder B1C is mixed with the cement Cn2 as a partial substitute for the fine aggregate FA during the production of the cement kneaded body Cn3, the amount of chlorine contained in the cement kneaded body Cn3 can be kept within the regulated value.
[0097] As described above, the coarse powder B1C separated from the biomass ash (raw ash) B1 in the classification step S10 has a relatively low amorphous content. Therefore, even if it is mixed with the cement Cn2 as a partial substitute for the fine aggregate FA during the production of the cement kneaded body Cn3, it is unlikely to expand due to the alkali-silica reaction.
[0098] As described above, the coarse powder B1C separated from the biomass ash (raw ash) B1 in the classification step S10 has a relatively low content of sulfur oxides. Therefore, even if the coarse powder B1C is mixed with the cement Cn2 as a partial substitute for the fine aggregate FA during the production of the cement kneaded body Cn3, the setting of the cement kneaded body Cn3 is not accelerated beyond the desired state, and the quality of the hardened cement product can be homogenized.
[0099] As described above, the coarse powder B1C separated from the biomass ash (raw ash) B1 in the classification step S10 has a relatively low ignition loss and a small amount of unburned carbon. Therefore, even if it is mixed with the cement Cn2 as a partial substitute for the fine aggregate FA during the production of the cement kneaded body Cn3, it is unlikely that the resulting hardened cement product will become black.
[0100] The above-mentioned feeding step S20 in the process for producing the cement kneaded body Cn3 corresponds to the step (b).
[0101] (Injection process S30: during cement production) The fine powder B1F obtained in the classification step S10 is input (added) to the raw material of the cement clinker Cn1, or to the cement clinker Cn1 or the cement Cn2. In the example of FIG. 2, the fine powder B1F is input to the clinker production facility 10 and to the crushing facility 31 for producing the cement Cn2. In the latter case, the fine powder B1F is crushed together with the cement clinker Cn1 to produce a mixed cement. At that time, water is sprinkled or a crushing aid is added as necessary. However, the fine powder B1F may be input to either the clinker production facility 10 or the crushing facility 31. However, if all the obtained fine powder B1F is input, it is the same as inputting the raw powder of the biomass ash (raw ash B1) as it is. Therefore, by taking advantage of the differences in the chemical composition and other properties of the classified biomass ash (i.e., the coarse powder B1C and the fine powder B1F), the fine powder B1F may be partially added to the raw material for cement clinker Cn1, the cement mixture, or the concrete admixture, or may be added after washing with water as described below.
[0102] As the pulverizing equipment 31, a general mill used in a finishing process such as a tube mill can be used. The mill is also called a finishing pulverizer, in which steel balls, cement clinker Cn1, and gypsum added as necessary collide with each other in a cylindrical drum as the drum rotates, and are pulverized. When gypsum is used, the gypsum is not particularly limited, and examples thereof include natural dihydrate gypsum, flue gas desulfurization gypsum, phosphate gypsum, titanic gypsum, and hydrofluoric gypsum. These may be used alone, or two or more types may be used in combination.
[0103] The fine powder B1F is used to replace a part of the cement raw materials. When it is fed into the pulverizing equipment 31, it is preferable to add it in an amount of 0.5% by mass to 30% by mass relative to the mass of the cement clinker Cn1. In addition, it is preferable to add gypsum in an amount of 1.5% by mass to 5.0% by mass calculated as SO3 in order to improve the strength development and fluidity of the cement Cn2.
[0104] As another method, the fine powder B1F obtained in the classification step S10 may be directly charged into the clinker cooler 13. An example of a charging method is to drop the powder from the top of the clinker cooler 13 to a position in the clinker cooler 13 at a desired temperature. The charging amount is preferably set to about 0.5% by mass to 20% by mass with respect to the mass of the cement clinker Cn1. Note that it is preferable to use an air quenching cooler as the clinker cooler 13, since the fine powder B1F can be charged to a predetermined position in the clinker cooler 13.
[0105] As described later in the second embodiment, when the fine powder B1F is charged after being washed with water, it is advantageous to charge it into the clinker cooler 13, since the moisture can be evaporated and removed by utilizing thermal energy that is not directly related to the production of the cement clinker Cn1. In order to prevent a large amount of dust from being generated in the clinker cooler 13, the fine powder B1F is preferably set to have a moisture content of 50 mass% or less and is preferably charged in the form of lumps or granules.
[0106] Although not shown in Fig. 2, the fine powder B1F may be added to the cement Cn2 obtained by pulverization in the pulverization equipment 31. Specifically, the timing of this addition may be on the route to the cement silo in which the cement is stored downstream of the pulverization equipment 31, or may be inside the cement silo. However, more strictly speaking, it is preferable to add the fine powder B1F to the cement clinker Cn1 or the pulverization equipment 31, since the fine powder B1F has a finer particle size and is more reactive, than to mix it with the cement Cn2 obtained after the cement clinker Cn1 is pulverized in the pulverization equipment 31.
[0107] The above-mentioned input step S30 in the production process of the cement Cn2 corresponds to the step (f1).
[0108] [Second embodiment] A second embodiment of the method for producing a cement kneaded body and cement will be described, focusing on differences from the first embodiment. Fig. 4 is a diagram that shows a process flow of the production method in this embodiment. Fig. 5 is a diagram that shows an example of a detailed process flow of a water washing step S40 described later. Fig. 6 is a block diagram that shows a production system 1 for carrying out the production method of this embodiment, following Fig. 2.
[0109] The manufacturing system 1 of this embodiment shown in Fig. 6 differs from the first embodiment in that it includes a water washing facility 40. The water washing facility 40 is a facility for washing the biomass ash B1 with water, and is provided for the purpose of reducing the concentration of cement-repellent components, such as chlorine, contained in the biomass ash B1. An example of a detailed structure of the water washing facility 40 will be described later with reference to Fig. 7.
[0110] In the process flow shown in Fig. 4, the water washing step S40 is performed only on the fine powder B1F obtained after the classification step S10. This is because, as described above in the first embodiment, the biomass ash (raw ash) B1 is classified in the classification step S10, so that the chlorine content of the coarse powder B1C is reduced, while the chlorine content of the fine powder B1F is relatively high. However, as described below, the water washing step S40 may also be performed on the coarse powder B1C, or the water washing step S40 may be performed together with the classification step S10.
[0111] (Water washing process S40) In this embodiment, fine powder B1F obtained by classifying biomass ash (raw ash) B1 in the classification step S10 is subjected to a water washing process by a water washing facility 40. More specifically, as shown in Fig. 5, a step S41 of forming a slurry from the fine powder B1F, a step S42 of washing the slurry with water, and a step S43 of dehydrating the slurry are carried out.
[0112] As an example, the water washing equipment 40 shown in FIG. 7 includes a powder dissolving tank 43 for adding water W2 to the fine powder B1F obtained after classification to form a slurry Lr1 for water washing, a solid-liquid separation device 46 for dewatering the slurry Lr2 discharged from the powder dissolving tank 43 after water washing, and a transport device 47 for transporting the dehydrated material Ck1 separated in the solid-liquid separation device 46.
[0113] 7, a liquid supplying device 42 for supplying water W2 is provided. A slurry mixing device 44 equipped with a mixing blade is provided for mixing the fine powder B1F and the water W2 and for mixing the slurry Lr1 produced by the mixing.
[0114] In the powder dissolution tank 43, a slurrying step S41 is performed in which the fine powder B1F and water W2 are mixed and stirred to produce a slurry Lr1, and a water washing step S42 is performed in which cement-repellent components such as chlorine are dissolved in the slurry Lr1 into the liquid phase. As the slurry stirrer 44 for this purpose, for example, a general stirrer such as a paddle type or a screw type can be used.
[0115] In the slurrying step S41, the mass ratio (W2 / B1F) of the fine powder B1F to the water W2 is preferably 2 to 10, more preferably 3 to 7, and particularly preferably 4 to 5. If the mass ratio (W2 / B1F) is less than 2, the modification effect may be insufficient, such as insufficient elution of water-soluble components such as chlorine from the fine powder B1F. If the mass ratio (W2 / B1F) is greater than 10, the amount of wastewater W4 increases.
[0116] The water washing step S42 is performed by leaving the slurry Lr1 to stand or stirring it for a predetermined time, thereby obtaining a slurry Lr2 in which the soluble components of the fine powder B1F are dissolved in the liquid phase of the slurry.
[0117] The time required for the water washing step S42 is preferably 30 minutes or more, more preferably 45 minutes or more, in order to sufficiently modify the fine powder B1F with the water W2. The higher the temperature during the water washing step S42, the more efficient the elution of water-soluble components such as chlorine from the fine powder B1F becomes, but from the viewpoint of the cost of the treatment, the temperature is preferably 5°C to 50°C, more preferably 25°C to 50°C.
[0118] After the water washing step S42, the slurry Lr2 in which cement-repellent components such as chlorine have been dissolved into the liquid phase in the slurry is discharged from the powder dissolving tank 43 and transferred to a solid-liquid separation device 46. A normal slurry liquid transport device (not shown) such as a slurry centrifugal pump, piston pump, or mono pump may be used to transport the slurry Lr2.
[0119] The solid-liquid separator 46 separates the slurry Lr2 into solid and liquid to obtain a dehydrated product Ck1 (dehydration step S43). As the solid-liquid separator 46, a typical filtration device such as a filter press, a pressurized leaf filter, a screw press, a belt press, a belt filter, or a sedimentation separator can be used.
[0120] In the dehydration step S43, in order to prevent water-soluble components such as chlorine contained in the slurry Lr2 from remaining together with the liquid phase, the moisture content of the dehydrated product is preferably 20% by mass to 90% by mass, and more preferably 30% by mass to 70% by mass.
[0121] The components eluted into the liquid phase of the slurry Lr2 are removed into the wastewater W4, so that the obtained dehydrated product Ck1 has a reduced amount of cement-repellent components such as chlorine compared to the fine powder B1F before the execution of the water washing step S40. On the other hand, since the heavy metals and the like contained in the biomass ash B1 are also eluted into the wastewater W4, it may be discharged into the environment after performing an appropriate water purification treatment.
[0122] 7, a water washing device 49 may be provided to the solid-liquid separator 46, and water W3 may be added to the dehydrated product Ck1, followed by dehydration again. In this way, most of the liquid phase of the slurry Lr2 is replaced with water, so that the eluted components can be removed more reliably.
[0123] This water washing step S40 corresponds to step (c).
[0124] The dehydrated material Ck1 obtained through the water washing step S40 has a reduced amount of cement-repelling components such as chlorine, and a sufficiently reduced amount of easily reactive calcium oxide and calcium hydroxide that affect the strength development and fluidity of the cement Cn2. Therefore, by using the dehydrated material Ck1 derived from the fine powder B1F and adding it to the raw material of the cement clinker Cn1, or to the cement clinker Cn1 or the cement Cn2, as in the first embodiment, it becomes easy to maintain the quality of the obtained cement Cn2 homogeneous. In particular, when biomass ash B1 discharged from a fluidized bed combustion furnace to which limestone containing a calcium component is added is used as raw ash, the above effect can be significantly achieved.
[0125] In addition, the dehydrated material Ck1 derived from the fine powder B1F obtained through the water washing step S40 may contain more moisture than the fine powder B1F obtained in the first embodiment. Therefore, by feeding this dehydrated material Ck1 into the pulverization equipment 31, it can also be used to control the temperature in the pulverization equipment 31. If the moisture contained in the dehydrated material Ck1 is excessive, it can be easily dehydrated by sedimentation or the like, and conversely, if the moisture is insufficient, an appropriate amount of water can be sprayed on the pulverization equipment 31.
[0126] The wastewater W4 obtained in the dewatering step S43 may be mixed with the cement clinker Cn1 in a state in which the chlorine ion content has been reduced by a known method such as ion exchange resin, membrane separation, precipitation with silver or lead ions, etc. This makes it possible to effectively utilize the alkali metals contained in the wastewater W4 that have a strength-enhancing effect while removing chlorine that causes rebar corrosion. As in this embodiment, the dehydrated product Ck1 derived from the fine powder B1F obtained by performing the water-washing step S40 becomes less active due to water washing, so the reduced activity can be compensated for by adding the wastewater W4 after water washing as a cement additive.
[0127] Biomass ash B1 has a lower chlorine content than municipal waste incineration ash. Therefore, the chlorine contained in wastewater W4 can be easily separated, and a large amount of alkali metal sulfates and carbonates can be obtained in the wastewater W4. Therefore, by introducing wastewater W4 on the route from the clinker cooler 13 to the pulverizing equipment 31, more alkali metals can be used as cement additives.
[0128] By introducing the wastewater W4 on the path from the clinker cooler 13 to the pulverizing equipment 31, it is possible to use it for cooling the cement clinker Cn1 and for sprinkling water for adjusting the temperature in the pulverizing equipment 31 without drying or solidifying. More specific introduction points include the clinker cooler 13 at 400°C or less in the clinker production equipment 10, the conveying device for conveying from the clinker cooler 13 to the subsequent stage, and the pulverizing equipment 31. If the temperature at the introduction point exceeds 400°C, it will evaporate instantly, making it difficult for alkali metals as cement additives to be contained in the cement Cn2. In addition, if the wastewater W4 is introduced at a stage subsequent to the pulverizing equipment 31, moisture will remain in the cement Cn2, and the quality may be reduced due to the effects of weathering and hydration.
[0129] The wastewater W4 may be subjected to a drying process or the like to reduce the moisture content, and then fed between the clinker cooler 13 and the pulverizing equipment 31. This allows more alkali metals to be used as cement additives without causing the cement Cn2 to weather. In particular, if the wastewater W4 is dried and solidified, it can be fed to the cement Cn2 obtained after pulverization in the pulverizing equipment 31, or during the kneading process carried out in the mixing equipment 33, and any desired amount can be easily added.
[0130] As a means for reducing the amount of contained chloride ions, it is particularly preferable to use amphoteric ion exchange resins or nanofiltration membranes, which can selectively separate sulfate ions, carbonate ions, and chloride ions, and produce water with high sulfate ion and carbonate ion concentrations and low chloride ion concentrations, and water with low sulfate ion and carbonate ion concentrations and high chloride ion concentrations.
[0131] Wastewater W4 obtained after washing the fine powder B1F often contains selenium and hexavalent chromium. By using the above-mentioned amphoteric ion exchange resin and nanofiltration membrane, selenium and hexavalent chromium, which have the same form as sulfate ions, are separated into water with a low chlorine concentration. Water with a high chlorine concentration is disposed of, but this water also has low concentrations of selenium and hexavalent chromium, making wastewater treatment easier. In addition, the amount of water can be reduced (the alkali metal concentration can be increased) without drying, and if it is added between the clinker cooler 13 and the grinding equipment 31, more alkali metals can be used as cement additives with the same amount of water sprayed.
[0132] As described above, both the wastewater W4 (cement additive) obtained from the washing water and the dehydrated product Ck1 obtained after washing the fine powder B1F can be used in the production process of cement Cn2. As described above in the first embodiment, the coarse powder B1C can be used as a partial substitute for the fine aggregate FA when producing the cement kneaded body Cn3. This allows the biomass ash B1 to be used in the production of cement Cn2 and the cement kneaded body Cn3 without any waste. In addition, the amount of wastewater to be disposed of and the wastewater treatment load can be reduced.
[0133] In this embodiment, it is also possible to execute the oxidation step S51 and the unburned carbon removal step S52 together with the water-washing step S40 (see FIGS. 8 and 9). These steps may be executed in parallel with the water-washing step S40, or may be executed after the water-washing step S40. It is also possible to execute only one of the oxidation step S51 and the unburned carbon removal step S52.
[0134] Fig. 8 is a diagram showing a typical process flow in the case where both the oxidation step S51 and the unburned carbon removal step S52 are performed in this embodiment. Fig. 9 is a diagram showing a typical structure of the water washing equipment 40 in the case where these steps S51 and S52 are performed, following Fig. 7. Note that Fig. 9 also shows a gas supplying device 51 and a flotation device 53 in addition to the water washing equipment 40.
[0135] (Oxidation step S51) The oxidation step S51 is a step of oxidizing the fine powder B1F. As an example, the water washing step S40 can be performed by adding a pH adjuster to the powder dissolving tank 43 and washing with water. In this way, the water washing step S40 and the oxidation step S51 are performed in parallel.
[0136] By reducing the pH during washing, the chlorine contained in the fine powder B1F can be dissolved in water more efficiently than when the pH is not adjusted. In addition, the calcium component contained in the fine powder B1F can be easily converted into calcium carbonate, which reacts slowly, or into calcium sulfate, which is added to the cement clinker Cn1 during the production of cement Cn2. As a result, the dehydrated product Ck1 derived from the fine powder B1F obtained after the washing step S40 becomes suitable as a cement admixture with little quality variation.
[0137] The pH condition of the slurry Lr1 in the oxidation step S51 is preferably pH 4-13, and more preferably pH 5-12.
[0138] There are no particular limitations on the pH adjuster as long as it can reduce the pH of the slurry Lr1, and examples include an acid solution such as sulfuric acid and a CO2-containing gas. Examples of CO2-containing gas include combustion exhaust gas from the cement kiln 12, and combustion exhaust gas from biomass incineration equipment and biomass power plants. These exhaust gases contain carbon dioxide (CO2), so the pH can be adjusted from neutral to weakly alkaline by injecting the combustion exhaust gas into the slurry Lr1. This makes it easier for the calcium component contained in the fine powder B1F to react by carbonate to form calcium carbonate.
[0139] 9 shows, as an example, a case in which a CO2-containing gas G1 is supplied from a gas supply device 51 to a slurry Lr1 in a powder dissolving tank 43. In this case, the gas supply device 51 corresponds to the device for supplying the above-mentioned combustion exhaust gas from the cement kiln 12, or the combustion exhaust gas from a biomass incineration facility or a biomass power plant to the powder dissolving tank 43.
[0140] The CO2-containing gas G1 may contain carbon dioxide, but in order to promote efficient carbonation, the carbon dioxide concentration is preferably 10% or more, more preferably 20% or more. In addition, among the combustion exhaust gases, the gas after collecting the chlorine bypass dust from the clinker manufacturing facility 10 contains sulfur oxides (SO x ) and other harmful gases, so by injecting this gas into the slurry Lr1, it is expected that the effect of immobilizing the sulfur oxides can also be achieved.
[0141] In this way, by using the combustion exhaust gas from the clinker production facility 10, the combustion exhaust gas containing carbon dioxide can be obtained on-site and used to reform the fine powder B1F, and the reformed fine powder B1F (dehydrated material Ck1) can be used as a cement admixture. Also, by using the combustion exhaust gas from a biomass incineration facility or a biomass power plant, the fine powder B1F can be reformed using the combustion exhaust gas containing carbon dioxide obtained on-site, and if this is transported to the clinker production facility 10 or the crushing facility 31, it can be immediately used as a cement admixture.
[0142] Furthermore, in the water washing step S40, water washing may be performed by adding waste liquid obtained from an amine-based carbon dioxide recovery apparatus into powder dissolution tank 43. In an amine-based carbon dioxide recovery apparatus for recovering carbon dioxide from exhaust gas from a factory or the like, liquid containing deteriorated amines is usually discarded, but this method makes it possible to effectively utilize the waste liquid.
[0143] Amines are known to react with carbon dioxide to promote the generation of carbonate ions, and can efficiently promote the carbonation of calcium components. Amines are also known to function as grinding aids when grinding cement clinker Cn1 in the grinding equipment 31. Amines have an amino group and a hydroxyl group in the molecule, and examples of amines used as grinding aids include monoethanolamine (MEA), diethanolamine (DEA), triethanolamine (TEA), diglycolamine (DGA), diisopropanolamine (DIPA), methyldiethanolamine (MDEA), and triisopropanolamine (TIPA). Therefore, the dehydrated product Ck1 derived from the fine powder B1F, which has amines brought in from the added waste liquid, is expected to have functionality as a grinding aid in the subsequent process, and is therefore suitable as a cement admixture.
[0144] In addition, CO2-containing gas G1 may be blown into the dehydrated material Ck1 obtained through the dehydration step S43. This will carbonate the easily reactive calcium components remaining in the dehydrated material Ck1, and will further homogenize the quality of the cement Cn2 produced using the dehydrated material Ck1. This method is also expected to have the effect of drying the water contained in the dehydrated material Ck1.
[0145] The gas injection means (gas supply device 51) may be any method that can bring the dehydrated material Ck1 into contact with the CO2-containing gas. For example, a CO2-containing gas may be passed through a container filled with the dehydrated material Ck1, or the dehydrated material Ck1 may be passed through an exhaust gas duct. In addition, as with the injection into the slurry Lr1 described above, the combustion exhaust gas from the cement kiln 12 or the combustion exhaust gas from a biomass incineration facility or a biomass power plant may be injected into the dehydrated material Ck1.
[0146] This oxidation step S51 corresponds to step (d).
[0147] (Unburned carbon removal process S52) The unburned carbon removal step S52 is a step of removing unburned carbon contained in the fine powder B1F. As described above, the fine powder B1F obtained after classification has a higher ignition loss and contains a large amount of unburned carbon compared to the coarse powder B1C. Therefore, when the fine powder B1F is used as a raw material for cement clinker Cn1, it may cause the preheater 11 to become too hot, and when it is used as an admixture, it may cause the concrete to darken or the fluidity to decrease.
[0148] Specifically, during the water washing step S40, a method can be employed in which an unburned carbon removal agent D1 such as oil or a surfactant is added from an unburned carbon removal agent supply device 52 to a powder dissolution tank 43, and then stirring or other processing is performed in that state. The obtained slurry Lr2a is subjected to a flotation process in a flotation device 53, for example by adding a specific foaming agent, and is separated into a froth containing unburned carbon and a tail in which unburned carbon has been removed or reduced. The tail slurry Lr2b is then sent to a solid-liquid separation device 46 and separated into solid and liquid.
[0149] As a result, the water washing step S40 and the unburned carbon removal step S52 are carried out in parallel and successively.
[0150] This unburned carbon removal step S52 corresponds to step (e).
[0151] By carrying out the water washing step S40, the chlorine concentration (chlorine content) contained in the fine powder B1F is reduced, for example, typically to 0.01 mass % to 0.2 mass %, and more typically to 0.02 mass % to 0.1 mass %.
[0152] By carrying out the water washing step S40, the total alkali metal concentration contained in the fine powder B1F is typically reduced to, for example, 1% by mass to 8% by mass, and more typically reduced to 3% by mass to 6% by mass.
[0153] By carrying out the water washing step S40, the sulfur oxide concentration contained in the fine powder B1F is reduced, for example, typically to 0.5% by mass to 4% by mass, and more typically to 1% by mass to 3% by mass.
[0154] By carrying out the water washing step S40, the amount of eluted selenium (Se) in the fine powder B1F is reduced to, for example, typically 0.002 mg / L to 0.02 mg / L, more typically 0.005 mg / L to 0.01 mg / L. In addition, the amount of eluted hexavalent chromium (Cr 6+ ) The amount of elution is typically reduced to, for example, 0.01 mg / L to 0.1 mg / L, more typically 0.02 mg / L to 0.05 mg / L. The amounts of elution of these selenium and hexavalent chromium can be measured by known methods. As a preferred example of the measurement method, a test solution is prepared in accordance with JISK 0058-1 "Testing methods for chemical substances of slags - Part 1: Leaching test method 5. Testing in the form used", and then selenium is measured by ICP mass spectrometry and hexavalent chromium is measured by diphenylcarbazide absorptiometry.
[0155] In addition, the dehydrated product Ck1 derived from the fine powder B1F obtained by the method of this embodiment has a reduced alkali metal content by performing the water washing step S40, but it is assumed that the alkali metal content is still higher than that of coal ash. Therefore, if the dehydrated product Ck1 is used as a raw material for cement clinker Cn1, cement Cn2 with a high alkali metal content may be produced. In addition, the main component of the cement additive obtained from the wastewater W4 is an alkali metal salt. Therefore, if these are contained in large amounts in concrete (cement mixture Cn3), there is a possibility that an alkali-silica reaction will occur depending on the aggregate (CA, FA) used.
[0156] Therefore, when the dehydrated product Ck1 derived from the fine powder B1F is added in the manufacturing process of the cement Cn2, latent hydraulic substances such as blast furnace slag, and pozzolanic substances such as fly ash, volcanic ash, volcanic rock, and burnt clay may be added (added) together as cement admixtures or concrete admixtures in order to reduce the possibility of alkali-silica reaction. The addition (addition) of such latent hydraulic substances and pozzolanic substances can also be applied in the case where the fine powder B1F that has not been subjected to the water washing step S40 is used as in the first embodiment.
[0157] (Modification) In this embodiment, several variations are possible.
[0158] 10, the coarse powder B1C obtained after the classification step S10 may also be subjected to a water-washing step (water-washing step S40a). In this case, as shown in FIG. 11, the manufacturing system 1 may include a water-washing facility 40a for washing the classified coarse powder B1C. When performing the water-washing step S40a on the coarse powder B1C, a method similar to the water-washing step S40 on the fine powder B1F described above can be used. The dehydrated material Ck1 obtained after washing the coarse powder B1C is charged in the charging step S20 as a partial substitute material for the fine aggregate FA when the cement kneaded body Cn3 is produced.
[0159] As described above, the chlorine content of the coarse powder B1C is lower than that of the fine powder B1F, but by subjecting the coarse powder B1C to the water washing step S40a as in this embodiment, a further reduction in the chlorine content is expected.
[0160] 12, an oxidation step S51a and an unburned carbon removal step S52a may be performed together with the water washing step S40a. The oxidation step S51a and the unburned carbon removal step S52a can use the same methods as the oxidation step S51 and the unburned carbon removal step S52 described above, respectively.
[0161] The water washing step S40a corresponds to the step (c), the oxidation step S51a corresponds to the step (d), and the unburned carbon removal step S52a corresponds to the step (e).
[0162] <2> In the process flow shown in Fig. 10, the classification step S10 and the water washing step (S40, S40a) may be performed in parallel. In this case, the manufacturing system 1 is provided with a classification equipment 20 (40) equipped with a water washing function (see Fig. 13). In this case, a wet classifier is preferably used.
[0163] Furthermore, the raw ash (biomass ash B1) before classification may be subjected to a water washing step S40, and then the classification step S10 may be performed. In this case, wet classification is adopted for the classification step S10.
[0164] [Third embodiment] A third embodiment of the method for producing a cement kneaded body and cement will be described, focusing on differences from the first and second embodiments. Fig. 14 is a diagram that shows a process flow of the production method in this embodiment. Fig. 15 is a block diagram that shows a production system 1 for carrying out the production method of this embodiment, following Fig. 2. The production system 1 of this embodiment shown in Fig. 15 is different from the first embodiment in that it includes an analysis facility 61 and a pulverization facility 62.
[0165] (Analysis step S61) The coarse powder B1C obtained in the classification step S10 is analyzed in an analysis facility 61 to measure the amorphous ratio. This measurement may be performed on a portion extracted from the obtained coarse powder B1C. The analysis facility 61 includes an X-ray diffractometer and a calculation processing device, and the measurement method that can be suitably used is a method of calculating the results of X-ray diffraction measurement by Rietveld analysis (XRD-Rietveld method).
[0166] (Crushing process S62) As described above in the first embodiment, the coarse powder B1C obtained in the classification step S10 typically has an amorphous content of 60 mass% or less. This amorphous content is preferably 50 mass% or less, more preferably 40 mass% or less, and particularly preferably 30 mass% or less. However, depending on the properties of the biomass ash (raw ash) B1, the amorphous content of the coarse powder B1C obtained in the classification step S10 may be relatively high.
[0167] If the analysis result in the analysis step S61 indicates that the amorphous content of the coarse powder B1C is higher than the reference value, the coarse powder B1C is pulverized by pulverization equipment 62. As the pulverization equipment 62, equipment similar to the pulverization equipment 31 can be used.
[0168] If coarse powder B1C, whose amorphous content exceeds the standard value, is used as a partial substitute for fine aggregate FA in the production of cement mixture Cn3, there is a possibility that the cement mixture Cn3 may cause an alkali-silica reaction. On the other hand, this coarse powder B1C is obtained after classification of biomass ash B1, and has low calcium, sulfur, chlorine, and carbon contents, and is close to the composition of coal ash. Therefore, it can be used as a raw material for cement clinker Cn1 and as an admixture in the production of cement Cn2.
[0169] Since the coarse powder B1C has a large particle size as is, it is pulverized in a pulverization step S62, and the resulting pulverized coarse powder B2C is added to the production process of cement Cn2. This pulverization step S62 corresponds to step (g), and step S30, in which the pulverized coarse powder B2C is added to the production process of cement Cn2, corresponds to step (f2).
[0170] However, when the coarse powder B1C is fed into the pulverizing equipment 31, the pulverizing equipment 62 is not necessarily required. When the coarse powder B1C is used as a raw material for the cement clinker Cn1, the pulverizing equipment 62 may be a raw material pulverizer in the clinker production facility 10.
[0171] [Another embodiment] In the above embodiment, the coarse powder B1C and the fine powder B1F obtained after classifying the biomass ash B1 are both used to produce the cement Cn2 or the cement kneaded body Cn3. However, the scope of the present invention is when the coarse powder B1C obtained after classifying the biomass ash B1 is used at least in the production of the cement kneaded body Cn3. In other words, the fine powder B1F may be used for other purposes. EXAMPLES
[0172] [Verification 1] We obtained incineration fly ash BA-1 (particle size D50 47.2μm, ignition loss at 975℃ 4.17%) (biomass ash B1) from biomass power generation facility P1, which uses palm kernel shells as fuel to generate electricity in a circulating fluidized bed furnace, and investigated the effect of classifying this on the composition of the biomass ash. The coal content of the palm kernel shell and coal mixed fuel was 10 mass%. The particle size distribution of this incineration fly ash BA-1 (laser diffraction particle size distribution measurement device: Microtrac Bell MT3300EX II was used) is shown in Figure 3.
[0173] Test Method The test method is described below.
[0174] <1. Classification> Biomass ash B1 was sieved using a sieve (Spin Air Sieve: Seishin Enterprise SAR-75 / 200) with openings set to achieve the classification points shown in Table 1, and fine powder B1F was obtained as the sieve-passing fraction, and coarse powder B1C was obtained as the sieve-remaining fraction. This process corresponds to the classification step S10. The classification points were set based on the particle size distribution shown in Figure 3. In the test, biomass ash B1 was classified at three classification points of 32 μm, 45 μm, and 90 μm. In the following, biomass ash B1 may be referred to as "raw ash B1" to clarify that it is before classification.
[0175] The particle size distribution of the biomass ash after classification is shown in Table 1. Table 1 also shows the coarse powder B1C obtained after classifying the incineration fly ash BA-2 obtained from a different biomass power generation facility P2, with a classification point of 45 μm. The particle size distribution was measured using a laser diffraction particle size distribution analyzer (Microtrac-Bell MT3300EX II).
[0176] [Table 1]
[0177] 2. Mineral composition analysis The mineral compositions of raw ash B1 (symbol #1) derived from incineration fly ash BA-1, coarse powder B1C (symbol #2) obtained by classifying raw ash B1 at 45 μm, fine powder B1F (symbol #3) obtained by classifying raw ash B1 at 45 μm, coarse powder B1C (symbol #6) obtained by classifying raw ash B1 at 90 μm, and coarse powder B1C (symbol #8) derived from incineration fly ash BA-2 were measured using the XRD / Rietveld method.
[0178] In addition, the raw ash B1 (symbol #1) derived from the incineration fly ash BA-1 was further added with 20% by mass (water content 16.7% by mass) of water, stored at 20°C for 3 days, and dried at 105°C to obtain wet ash, and the mineral composition was measured in the same manner. This biomass ash is designated "symbol #1W". Furthermore, the mineral composition was measured in the same manner for the coarse powder B1C (designated "symbol #2W") obtained by classifying the wet ashed raw ash B1 (#1W) at 45 μm. In addition, an air jet sieve (e200LS, manufactured by Hosokawa Micron Corporation) was used to classify the wet ashed raw ash B1 (#1W).
[0179] First, the X-ray diffraction patterns of the biomass ash corresponding to each code (#1, #2, #3, #6, #8, #1W, #2W) were measured using an X-ray diffractometer (D8 ADVANCE A-25 manufactured by Bruker AXS) with 10% corundum (Al2O3) added as an internal standard. The measurement conditions for X-ray diffraction were CuKα radiation, tube voltage 50 kV, tube current 40 mA, scan range 5°-65° (2θ), step width 0.0234, and scan speed 0.13 sec / step. Next, Rietveld analysis was performed using the obtained diffraction patterns with software (TOPAS Ver.6.0 manufactured by Bruker AXS) to obtain quantitative results of the mineral composition.
[0180] From the obtained results, the amorphous volume was calculated from the quantitative value of corundum using the following formula (1). G = 100·(AR) / {A·(100-R) / 100} …(1) In formula (1), G is the amorphous mass (%), R is the mixture ratio of Al2O3 (%), and A is the quantitative value of Al2O3 (%).
[0181] In addition, the quantitative results obtained from the Rietveld analysis were standardized so that the total amount of the composition excluding the quantitative value of corundum was 100%, and then the value was further standardized by the proportion excluding the amorphous mass from this value to determine the mineral composition of each biomass ash (#1, #2, #3, #6, #8, #1W, #2W).
[0182] The results of the mineral composition analysis are shown in Table 2.
[0183] [Table 2]
[0184] According to Table 1, the comparison results of #1 to #3 confirm that the coarse powder B1C obtained by the classification step S10 has a lower amorphous content than the fine powder B1F. The comparison results of #1W and #2W also confirm that the coarse powder B1C obtained by the classification step S10 has a lower amorphous content than the fine powder B1F in the wet ash.
[0185] Figure 16 shows a polarized microscope image of raw ash B1 derived from incineration fly ash BA-1. In detail, raw ash B1 was extracted and solidified with epoxy resin, and then cut into chips of about 20 mm x 30 mm to prepare mirror-polished slices with a thickness of about 20 μm. The mirror-polished slices were observed under a polarized microscope to confirm the substances that constitute the sample.
[0186] The image shown in FIG. 16 confirms that only a portion of the periphery of the quartz particle has melted and become vitrified (amorphous), and that the proportion of amorphous matter contained on the coarse powder side, which has a relatively large particle size, is low.
[0187] <3. Compressive strength test, 4. Alkali-silica reaction test> In accordance with JIS R 5201 "Physical Testing Methods for Cement," ordinary Portland cement, water, and fine aggregate were mixed to prepare mortar specimens, and compressive strength tests were conducted on these mortar specimens.
[0188] In addition, in accordance with JIS A 1146 "Test method for alkali-silica reactivity of aggregates (mortar bar method)", ordinary Portland cement, water, and fine aggregate were mixed to prepare mortar as a test specimen, and an alkali-silica reactivity test was performed on this mortar.
[0189] In Comparative Example 1, only mountain sand was used as fine aggregate. In Examples 1 to 5, a part of the fine aggregate was replaced with the biomass ash coarse powder B1C (#2, #6, #8) in Table 2 above at a specified replacement rate. The properties of the mountain sand NS used in the test are shown in Table 3. The results of the compressive strength test and the alkali-silica reaction test for Examples 1 to 5 and Comparative Example 1 are shown in Table 4.
[0190] [Table 3]
[0191] [Table 4]
[0192] According to Table 4, in both Examples 1 to 4 using coarse powder B1C (#2, #6) derived from incineration fly ash BA-1 and Example 5 using coarse powder B1C (#8) derived from incineration fly ash BA-2, the results of the alkali-silica reactivity test were in Class A, and it was confirmed that the alkali-silica reaction was unlikely to occur, as in Comparative Example 1 using only mountain sand NS. This is considered to be due to the fact that the amorphous ratio of each of the coarse powders B1C (#2, #6, #8) was suppressed to 60 mass% or less, thereby suppressing the reactivity to alkali metals to a low level. However, in Example 5, which has a relatively high amorphous ratio (48.2%) among Examples 1 to 5, the expansion coefficient in the mortar bar method is higher than that of the other Examples.
[0193] In addition, comparing Examples 1 to 3 in which the replacement rate of coarse powder B1C (#2) obtained by classification at the same classification point (45 μm) was changed, it can be seen that the higher the replacement rate, the higher the compressive strength of the mortar of the test specimen. This is presumably because the increase in the replacement rate increases the amount of amorphous matter within a range that does not promote alkali-silica reaction, increasing the reactivity with the cement paste and increasing the adhesive strength between the cement paste and the fine aggregate. Example 4, in which D10 exceeds 110 μm, has lower expansion coefficient and compressive strength than the other Examples.
[0194] <5. Chemical composition analysis> The chemical components of raw ash B1 (#1) from incineration fly ash BA-1, each coarse powder B1C (#2, #4), each fine powder B1F (#3, #5), the raw ash B1 wet-ashed (#1W), and the wet-ashed raw ash B1 (#1W) classified at 45 μm to obtain coarse powder B1C (#2W). The raw ash B1 was also classified at a 20 μm point to obtain coarse powder B1C (#9) and fine powder B1F (#10), and the chemical components of these were also measured. Furthermore, the raw ash B1 (#1) and the fine powder B1F (#3) classified at 45 μm were washed with water in the following manner (#1Wp, #3Wp), and the chemical components were measured in the same manner.
[0195] The procedure for the water washing process is as follows: This water washing process corresponds to step S40. (Step 1) 100 g of biomass ash (B1, B1F) and 400 g of tap water were placed in a beaker, slurried, and stirred at 400 rpm for 30 minutes with a stirrer. When pH adjustment was performed by introducing CO2 gas during washing, the flow rate was adjusted while monitoring the pH in the liquid with a pH meter. (Step 2) After stopping the stirring, the mixture was filtered using a Buchner funnel, and 400 g of tap water was added to the resulting cake on the filter paper to wash the slurry, which was then collected. (Step 3) The collected cake was naturally dried, the mass was measured, and various analyses were performed.
[0196] The chemical components were measured by the following methods. The chemical composition of each sample (#1-#5, #9-#10, #1W, #2W, #1Wp, #3Wp) was measured by the calibration curve (coal ash) method using a fluorescent X-ray analyzer (Rigaku, ZSX Primus II). In addition, the ignition loss (ig.loss) of each sample was measured according to JIS R 5202 "Chemical analysis method of cement".
[0197] The chemical composition analysis results for each sample (#1-#5, #9-#10, #1W, #2W, #1Wp, #3Wp) are shown in Table 5.
[0198] [Table 5]
[0199] According to the results in Table 5, when raw ash B1, which is dry ash, is classified using the point between the peaks on the fine and coarse side of the particle size distribution expressed as frequency as the classification point, most of the chlorine and sulfur components (SO3) are contained in the fine powder (B1F). It was also confirmed that the chlorine components can be efficiently removed by washing this with water. For this reason, it can be seen that the fine powder after washing is particularly suitable as a cement mixture. On the other hand, it was confirmed that the chlorine components can be efficiently removed from coarse powder B1C simply by classifying it.
[0200] On the other hand, when comparing the wet ashing of raw ash B1 (#1W) with the coarse powder B1C (#2W) classified at 45μm, it is confirmed that the degree of decrease in chlorine concentration due to classification is small. This is presumably because the wet ashing of raw ash B1 caused coagulation and hydration reactions, and the chlorine (Cl) content was absorbed into the hydrates that were generated, resulting in a decrease in the removal rate due to classification. Hydration reactions occurred in the wet ashing of raw ash B1 (#1W), and the ignition loss was greater than that of raw ash B1, which is dry ash.
[0201] 6. Physical Testing The Blaine specific surface area, flow value ratio, and activity index of raw ash B1 (#1) derived from incineration fly ash BA-1, coarse powder B1C (#2) obtained with a classification point of 45 μm, and fine powder B1F (#3) were measured by a method conforming to Appendix C of JIS A 6201 "Fly ash for concrete". Furthermore, the coarse powder B1C (#2) was pulverized in a mill to a particle size equivalent to that of the fine powder B1F, and the Blaine specific surface area, flow value ratio, and activity index were measured in the same manner. The pulverized material (#2C) obtained by pulverizing the coarse powder B1C is a simulation of the symbol B2C in Figure 14. The measurement results are shown in Table 6.
[0202] [Table 6]
[0203] According to Table 6, it was confirmed that when fine powder B1F obtained by classifying raw ash B1 was used as an admixture, the activity index was higher than when raw ash B1 was used. In addition, for coarse powder B1C, the Blaine specific surface area was 4000 cm 2 It was revealed that if the coarse powder B1C, which has a relatively high amorphous content, is crushed to a concentration of 0.01g or more, it can be used as a pozzolanic admixture with a higher reactivity than raw ash B1. This suggests that crushing coarse powder B1C, which has a relatively high amorphous content, can be used as an admixture for the more reactive cement Cn2.
[0204] [Verification 2] Fly ash (particle size D50 (frequency) 45.3μm, ignition loss at 750℃ (ig.loss) 2.3%) was obtained from biomass power generation facility P2, which uses woody biomass (thinned wood) as fuel to generate electricity in a circulating fluidized bed furnace. The effects of washing this with water and the presence or absence of an oxidation process (particularly a carbonation process) during washing on its component composition were examined. The washing method was the same as in Verification 1.
[0205] Table 7 below shows the levels of each water washing condition.
[0206] [Table 7]
[0207] "analysis" The obtained samples were analyzed by the following methods. Determination of Cl: After the sample was decomposed with nitric acid, it was measured by potentiometric titration. Quantitative analysis of K and Na: After acid decomposition of the sample, the content was measured by ICP emission spectrometry. Se,Cr 6+ Dissolution test: After preparing the test solution in accordance with JIS K 0058-1 "Test methods for chemical substances of slags - Part 1: Dissolution test method 5. Testing in the form used", Se was measured by ICP mass spectrometry, and Cr was measured by 100%. 6+ were measured by diphenylcarbazide spectrophotometry. Quantitative determination of C, Mg, Al, Si, P, S, Ca, and Fe: Samples dried at 40°C were measured using a fluorescent X-ray analyzer (FP method: fundamental parameter method).
[0208] The amount of calcium carbonate in the raw ash and the obtained sample was calculated by measuring the mass loss near 600°C to 700°C when about 50 mg of the sample was heated to 1000°C at a heating rate of 20°C / min in a nitrogen atmosphere, and calculating the ratio of the mass loss to the weight loss of the reagent (using a TG-DTA 2000SR manufactured by NETZSCH). The amount of calcium hydroxide in the raw ash and the obtained sample was calculated by measuring the endothermic heat near 400°C when about 50 mg of the sample was heated to 1000°C at a heating rate of 10°C / min in a nitrogen atmosphere, and calculating the ratio of the mass loss to the weight loss of the reagent (using a DSC404F3 manufactured by NETZSCH).
[0209] The measurement results are shown in Tables 8 and 9.
[0210] [Table 8]
[0211] [Table 9]
[0212] According to Table 8, it was confirmed that most of the chlorine is effectively removed by washing the raw ash with water, and when used as an admixture, after the cement hardens with water, it meets the allowable standard of 0.035 mass% or less, which is evaluated as having no risk of corroding reinforcing bars, etc. In other words, when the biomass ash after washing is classified, it is found that there is almost no chlorine in either the fine or coarse powder side.
[0213] Furthermore, according to Table 8, the water-soluble selenium and hexavalent chromium contained in the raw ash were effectively removed by washing with water, and it became clear that the risk of leaching of heavy metals is reduced when the raw ash is used as an admixture.
[0214] As shown in Table 9, the main components of this biomass ash are SiO2 and CaO, and it has become clear that it is useful as a highly reactive pozzolanic admixture.
[0215] According to the results of Level 2-2, it was revealed that washing with water while blowing in CO2 gas increased the CO2 content of the biomass ash after washing. Therefore, it is considered that at least a part of the components for adjusting pH were fixed in the ash after the washing operation, and calcium carbonate was generated. In addition, calcium hydroxide disappeared by washing with water while blowing in CO2 gas. In Table 9, a calcium hydroxide content of less than 0.01% means that it is below the detection limit.
[0216] Table 10 below shows the results of investigating the form of calcium components in the ash by XRD method.
[0217] [Table 10]
[0218] According to Tables 9 and 10, the presence of calcium compounds, CaO (quicklime), Ca(OH)2 (slaked lime), CaCO3 (calcium carbonate), and CaSO4 (gypsum), was confirmed in the raw ash as a form of calcium component. In contrast, in level 2-1, where the raw ash was washed without pH adjustment, the presence of CaO (quicklime) disappeared, and the presence of Ca(OH)2 (slaked lime) decreased. In level 2-2, where the raw ash was washed at pH 9 while injecting CO2 gas, the presence of CaO (quicklime) and Ca(OH)2 (slaked lime) disappeared, and calcium carbonate increased.
[0219] [Verification 3] Fly ash (particle size D50 (frequency) 20.0μm, ignition loss at 750℃ 6.1%) was obtained from biomass power generation facility P3, which uses wood pellets and palm kernel shells as fuel to generate electricity in a stoker furnace, and tests similar to those used in the verification were conducted. The results are shown in Tables 11 and 12. In level 3-2, sulfuric acid was added during washing to adjust the pH.
[0220] [Table 11]
[0221] [Table 12]
[0222] According to Table 11, it was confirmed that most of the chlorine was effectively removed by washing the raw ash with water, as in Verification 2, and that when used as an admixture, after the cement hardens with water, it meets the allowable standard of 0.035 mass% or less, which is evaluated as having no risk of corroding reinforcing bars, etc. In other words, when the biomass ash after washing is classified, it is found that there is almost no chlorine in either the fine or coarse powder side.
[0223] According to Table 12, this biomass ash is mainly composed of SiO2 and CaO, and it is clear that it is useful as a highly reactive pozzolanic admixture. Furthermore, it was clear that the SO3 content increases by adding sulfuric acid and washing with water. Therefore, it is considered that at least a part of the sulfuric acid component for adjusting the pH is fixed in the ash after the water washing operation. [Explanation of symbols]
[0224] 1: Manufacturing system 3: Raw material tank 5: Powder storage tank 10: Clinker manufacturing facility 11: Preheater 12: Cement kiln 13: Clinker cooler 20: Classification equipment 31: Crushing equipment 33: Mixing equipment 40,40a: Washing equipment 42:Liquid supply device 43: Powder dissolving tank 44: Slurry mixing device 46:Solid-liquid separator 47:Transportation equipment 49: Water cleaning device 51: Gas supply equipment 52: Unburned carbon removal agent supply device 53: Flotation equipment 61:Analysis equipment 62: Crushing equipment B1: Biomass ash (raw ash) B1C: Coarse powder B1F: Fine powder B2C: Coarse crushed powder Ck1: Dehydrated product Cn1: Cement clinker Cn2: Cement Cn3: Cement mix D1: Unburned carbon removal agent FA: Fine aggregate G1: CO2-containing gas Lr1, Lr2, Lr2a, Lr2b: Slurry W1,W2,W3:Water W4: Drainage Y1: Cement clinker raw material
Claims
1. A step (a) of classifying the biomass ash into coarse powder and fine powder using a standard value in the range of 30 μm to 100 μm as a classification point; and a step (b) of mixing the coarse powder obtained in the step (a) with cement and water without grinding the coarse powder, The coarse powder obtained in the step (a) has a chlorine (Cl) content of 0.2 mass% or less before the water washing treatment, The method for producing a cement kneaded body, wherein the step (b) is a step of mixing the coarse powder having an amorphous ratio of 60 mass % or less with cement and water.
2. A step (a) of classifying the biomass ash into coarse powder and fine powder using a standard value in the range of 30 μm to 100 μm as a classification point; and a step (b) of mixing the coarse powder obtained in the step (a) with cement and water without grinding, The coarse powder obtained in the step (a) has a chlorine (Cl) content of 0.2 mass% or less before the water washing treatment, The method for producing a cement kneaded body, wherein the step (b) is a step of mixing the coarse powder with an adjusting powder, which is a powder made of other biomass ash having a lower amorphous content than the coarse powder, so that the amorphous content in the mixture of the coarse powder and the adjusting powder is adjusted to be 60 mass% or less, and then mixing the mixture with cement and water.
3. The method includes a step (c) of washing the coarse powder obtained in the step (a) with water, 3. The method for producing a cement kneaded body according to claim 1, wherein the step (b) is a step of mixing the coarse powder after the washing with water in the step (c).
4. The method for producing a cement kneaded body according to claim 3, further comprising a step (d) of oxidizing the biomass ash during or after the step (c).
5. The method for producing a cement kneaded body according to claim 3 or 4, further comprising a step (e) of removing unburned carbon contained in the biomass ash during the execution of the step (c).
6. 3. The method for producing a cement kneaded body according to claim 1, further comprising a step (f1) of feeding the fine powder obtained in the step (a) to at least one of a cement clinker raw material to be fed into a cement kiln, a cement clinker obtained from the cement kiln, or a cement obtained after a grinding treatment of the cement clinker.
7. A step (c) of washing the biomass ash with water before or after carrying out the step (a), 7. The method for producing a cement kneaded body according to claim 6, wherein the step (f1) is a step of adding the fine powder after being washed with water in the step (c).
8. The method includes a step (g) of pulverizing the coarse powder obtained in the step (a) having an amorphous ratio of more than 60 mass%, 8. The method for producing a cement kneaded body according to claim 6 or 7, further comprising a step (f2) of introducing the coarse powder pulverized in the step (g) into at least one of the cement clinker raw material, the cement clinker, or the cement obtained after a pulverization treatment of the cement clinker.
Citation Information
Patent Citations
Amorphous chaff ash and manufacture of hydraulic cement andforming material from chaff ash as raw material
JP1985036360A
Cement admixture, production of blended cement and device therefor
JP1996268740A
Method and apparatus for disposing exhaust gas in cement firing facility
JP2006089298A
Combustion device and combustion ash treatment method
JP2017122550A
Burned ash particle, organosilicon material, abrasive, and method for manufacturing organosilicon material
JP2018058717A